Digitising Afrikaans: Establishing a protocol for digitalizing historical sources for Early Afrikaans (1675-1925) as a possible template for indigenous South African languages (Journal of the Digital Humanities Association of Southern Africa, 2022)
Afrikaans is one of South Africa’s 11 official languages. With the continued rise of English as language of prestige in education, the economy and public sphere a movement towards a monolingual South Africa seems to be underway. This movement results in a loss of interest in the development and use of South Africa’s indigenous languages. Another contributing factor is the unavailability or inaccessibility of resources in indigenous South African languages.This paper reports on the protocol and process of establishing online resources to encourage research in and on Afrikaans. The digitalisation process encompasses establishing a) digital bibliographies for Afrikaans literature and linguistics, where researchers can find links to online resources and pdf documents; b) an online archive where endangered (and often otherwise unobtainable) resources are stored in digital format; c) an online library where digitalized machine readable texts are stored; and d) an online historical corpus for Early Afrikaans (1675-1925). These resources are all angled towards linguistic research, specifically corpus linguistic research. VivA also offers a number of online resources to make research in Afrikaans more accessible – these include a general and school grammar for Afrikaans, a corpus portal for corpus linguists, and a speech atlas to create awareness of linguistic variety in Afrikaans.The digitisation project is largely based on the Digital Library for Dutch Literature (Dutch: Digitale Bibliotheek voor de Nederlandse Letteren) (DBNL) and is still ongoing with various phases being undertaken simultaneously. It is our goal to present this project as a template to demonstrate how other indigenous South African languages can go about establishing digital resources and to encourage synergy amongst linguists and linguistic institutions.
Keywords: digitisation process; digital archive; digital bibliography; historical corpus; Early Afrikaans 1675-1925